Ecologies of Repair: A Post-human Approach to Other-Than-Human Natures - Blanco-Wells, Gustavo (Frontiers in Psychology, 2021)
This conceptual paper explores the theoretical possibilities of posthumanism and presents ecologies of repair as a heuristic device to explore the association modes of different entities, which, when confronted with the effects of human-induced destructive events, seek to repair the damage and transform the conditions of coexistence of various life forms. The central idea is that severe socio-environmental crisis caused by an intensification of industrial activity are conducive to observing new sociomaterial configurations and affective dispositions that, through the reorganization of practices of resistance, remediation, and mutual care, are oriented to generating reparative and/or transformative processes from damaged ecologies and communities. Crises constitute true ontological experimentation processes where the presence of other-than-human natures, and of artifacts or devices that participate in reparative actions, become visible. A post-human approach to nature allows us to use languages and methodologies that do not restrict the emergence of assemblages under the assumption of their a priori ontological separation, but rather examine their reparative potential based on the efficacy of situated relationships. Methodologically, transdisciplinarity is relevant, with ethnography and other engaged methods applied over units of observation and experience called socio-geo-ecologies. The relevant attributes of these socio-geo-ecologies, beyond the individual, community, or institutional aspects, are the specific geological characteristics that make possible an entanglement of interdependent relationships between human and non-human agents. The conceptual analysis is illustrated with empirical examples stemming from socio-geo-ecologies researched in Southern Chile.